The house of Augustus : a historical detective story - Wiseman, T. P. (Princeton University Press, 2019)
This book serves as a reexamination of the textual and archaeological evidence about Augustus and the Palatine. Caesar Augustus (63 BC-14 AD), who is usually thought of as the first Roman emperor, lived on the Palatine Hill, the place from which the word "palace" originates. A reassessment of textual and archaeological evidence, this book demonstrates that Augustus was never an emperor in any meaningful sense of the word, that he never had a palace, and that the so-called "Casa di Augusto" excavated on the Palatine was a lavish aristocratic house destroyed by the young Caesar in order to build the temple of Apollo. Exploring the Palatine from its first occupation to the present, the author proposes a reexamination of the "Augustan Age," including much of its literature. The author shows how the political and ideological background of Augustus's rise to power offers a radically different interpretation of the ancient evidence about the Augustan Palatine. Taking a long historical perspective in order to better understand the topography, the author considers the legendary stories of Rome's origins - in particular Romulus's foundation and inauguration of the city on the summit of the Palatine. He examines the new temple of Apollo and the piazza it overlooked, as well as the portico around it with its library used as a hall for Senate meetings, and he illustrates how Commander Caesar, who became Caesar Augustus, was the champion of the Roman people against an oppressive oligarchy corrupting the Republic